How Long Can One Live Without a Permanent Pacemaker in Complete Heart Block? A Case Report from Rural Kenya (American Journal of Medical Science and Innovation, 2025)
Complete heart block is characterized by a total atrioventricular dissociation resulting in junctional or ventricular escape rhythms. It is associated with high cardiovascular mortality rates without definitive treatment. The current guidelines recommend the placement of a permanent pacemaker to manage all cases of a complete heart block not caused by reversible or physiological causes, irrespective of patient symptoms. The natural history and prognosis of complete heart block not treated with pacemaker placement are unknown. In this study, we present the case of an elderly woman from rural Kenya who was diagnosed with a complete heart block 30 years ago and recommended a permanent pacemaker but declined. She has lived a relatively normal and active life without a pacemaker, albeit with compensated heart failure. This case suggests that a subset of patients with complete heart block may have good clinical outcomes without the need for a permanent pacemaker. It would be worthwhile to do further studies to map this subset of patients’ natural history and prognostic factors.